Developments and clinical evaluations of robotic exoskeleton technology for human upper-limb rehabilitation. (2nd August 2020) - Gupta, Akash; Singh, Anshuman; Verma, Varnita; Mondal, Amit Kumar; Gupta, Mukul Kumar
Abstract : The development of upper limb and lower extremity robotic exoskeletons has emerged as a way to improve the quality of life as well as act as a primary rehabilitation device for individuals suffering from stroke or spinal cord injury. This paper contains extractions from the database of robotic exoskeleton for human upper limb rehabilitation and prime factors behind the burden of stroke. Various studies on stroke-induced deficiency from different countries were included in the review. The data were extracted from both clinical tests and surveys. Though there have been splendid advancements in this field, they still present enormous challenges. This paper provides the current developments, progress and research challenges in exoskeleton technology along with future research directions associated with the field of exoskeletons and orthosis. Robot-assisted training (RT) was found to be more effective than conventional training (CT) sessions. The present research articles in this field have many weaknesses as they do not cover the systematic review including the clinical studies and various surveys that lay a foundation for the requirement of robotic assistive devices. This review paper also discusses various exoskeleton devices that have been clinically evaluated. GRAPHICAL ABSTRACT: UF0001